Characterization of pyrene biodegradation by white-rot fungus polyporus SP. S133 - Hadibarata, Tony (2012)
A white-rot fungus of Polyporus sp. S133 was isolated from an oil-polluted soil. The metabolism of pyrene by this fungus was investigated in liquid medium with 5 mg of the compound. Depletion of pyrene was evident during the 30-day growth period and was 21% and 90%, respectively, in cometabolism and metabolism of pyrene alone. Pyrene was absorbed to fungal cells or biodegraded to form simpler structural compounds. Seventy-one percent of eliminated pyrene was transformed by Polyporus sp. S133 into other compounds, whereas only 18% was absorbed in the fungal cell. The effects of pH and temperature on biomass production of Polyporus sp. S133 for pyrene were examined; the properties of laccase and 1,2-dioxygenase produced by Polyporus sp. S133 during pyrene degradation were investigated. The optimal values of pH were 3, 5, and 4 for laccase, 1,2-dioxygenase, and biomass production, respectively, whereas the optimal values of temperature were 25 °C for laccase and 50 °C for 1,2-dioxygenase and biomass production. Under optimal conditions, pyrene was mainly metabolized to 1-hydroxypyrene and gentisic acid. The structure of 1-hydroxypyrene and gentisic acid was determined by gas chromatography-mass spectrometry after identification using thin-layer chromatography.